Willingness to pay (WTP) for area-based yield (ARBY) index insurance product - Raviz, Jeny; Gutierrez, Mary Anne; Laborte, Alice (International Rice Research Institute, 2024)
The CGIAR Initiative on Climate Resilience (ClimBeR) through collaboration among the Philippine Crop Insurance Corporation (PCIC), the Philippine Rice Research Institute (PhilRice), and the International Rice Research Institute (IRRI) has been developing and testing an innovative area-based yield (ARBY) index insurance for rice to de-risk the livelihood of smallholder farmers in the Philippines. This partnership builds on an earlier collaboration between IRRI and PhilRice that developed and operationalized a satellite-based rice mapping and monitoring system called PRISM (Philippine Rice Information System, https://prism.philrice.gov.ph/). ARBY is a type of crop insurance that provides coverage based on historical average yield of a specific geographic area, rather than individual farmer’s yields, to determine payouts in the event of crop losses. To design the ARBY insurance product, historical seasonal rice yield data from PRISM was used. During the 2023-2024 dry season, a pilot test of the ARBY insurance was conducted across six municipalities in the Philippines, including an assessment of farmers' willingness to pay (WTP) for crop insurance. An insurance awareness and orientation campaign for rice farmers was conducted before crop establishment to explain the existing indemnity-based crop insurance and introduce the ARBY insurance product. After the introduction, a baseline survey with farmers who participated in the orientation was conducted which included questions to assess farmers’ willingness to pay for crop insurance. At the end of the dry season, PhilRice provided PRISM data and assessment was made whether the yield trigger was breached and a “payout” was simulated in each of the six municipalities. Another meeting was conducted inviting the same farmers and the results of the simulation were presented. A post-season survey with farmers was conducted which included an assessment of their perception about the ARBY insurance.